Sub-satisfactory recanalization of severe middle cerebral artery stenoses can significantly improve hemodynamics - Zhang, Kun; Ren, Wei; Li, Tian-Xiao; Wang, Zi-Liang; Gao, Bu-Lang; Xia, Jin-Chao; Gao, Hui-Li; Wang, Yong-Feng; Gu, Jian-Jun (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To investigate the effect of sub-satisfactory stent recanalization on hemodynamic stresses for severe stenoses of middle cerebral artery (MCA) M 1 segment. Materials and methods: Patients with severe stenoses of MCA M1 segment treated with endovascular stent angioplasty were retrospectively enrolled. Three dimensional digital subtraction angiography before and after stenting was performed, and computational fluid dynamics (CFD) analysis of the hemodynamic stresses at the stenosis and normal segments proximal and distal to the stenosis were analyzed. Results: Fifty-one patients with severe stenosis at the MCA M1 segment were enrolled, with the stenosis length ranging 5.1-12.8 mm (mean 9.0±3.3). Stent angioplasty was successful in all patients (100%). Angiography immediately after stenting demonstrated significant (P<0.05) decrease in MCA stenosis after compared with before stenting (31.4%±12.5% vs. 87.5±9.6) , with a residual stenosis of 15%-30% (mean 22.4%±3.5% ). Before stenting, the total pressure was significantly (P<0.0001) higher while the WSS, velocity, and vorticity were all significantly (P<0.0001) decreased at the normal arterial segment proximal to the stenosis, and the total pressure, WSS, velocity, and vorticity were all significantly (P<0.0001) decreased at the normal arterial segment distal to the stenosis compared with those at the stenosis. After sub-satisfactory stenting recanalization, all the hemodynamic stresses at, proximal or distal to the stenosis, and at the perforator root were improved compared with those before stenting, similar to those after virtual stenosis removal. Conclusion: Sub-satisfactory recanalization of severe MCA stenoses can significantly improve the hemodynamic status at the stenoses for cerebral perfusion.